Compressive strength and water absorption of cement stabilized earth brick mixed with locust bean pod extract - P.P, Duru; J.M, Kaura; O.O, Akin; I.B, Raymond (International Journal of Advanced Geosciences, 2020)
This study presents the experimental investigation carried out on the compressive strength and water absorption properties of lateritic blocks stabilized with cement and locust bean pod extract. Tests were carried out in which different sample batches of cement blocks (0.1, 0.2, 0.3, 0.4 and 0.5kg) were moulded and different sample batches of locust bean pod extract blocks (50, 100, 133, 150 and 200g/litre) were moulded and with both cement and locust bean pod moulded too. The compressive strength of the lateritic block samples were tested at 28 days. The results indicated that the cement with locust bean pod extract significantly increase the compressive strength of the lateritic block samples. This compressive strength increases as the amount of cement and locust bean pod extract was increased. This is a validation of the high possibilities of both cement locust bean pod extract being utilized as a binder in the production of blocks for low housing construction in developing areas of Nigeria.Â